Assessment strategies for self-directed learning - Costa, Arthur L.; Kallick, Bena. (Thousand Oaks, Calif. ; London : Corwin, 2004)
This volume focuses on assessing students' abilities as self-directed learners. The authors use'triangulation' to ensure that the assessment system is balanced and complete.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Self-culture -- Evaluation